Comparative evaluation of in vitro techniques for predicting metabolizable energy content of total mixed ration for Murrah buffaloes - LAKHANI, NEETI; TYAGI, NITIN (The Indian Journal of Animal Sciences, 2021)
The present study was conducted to ascertain the sensitivity of in vitro techniques namely, in vitro gas production (IVGPT) and Cornell Net Carbohydrate and Protein System (CNCPS) fraction for predicting the metabolizable energy (ME) content of total mixed ration for Murrah buffaloes. The total mixed ration forming dietary treatment were TMR1, TMR2 and TMR3 having mixture of maize silage and concentrate in ratio of 30:70, 40:60 and 50:50, respectively. The diets formulated were isocaloric and isonitrogenous. The in vitro gas production was studied by incubation of diet with rumen liquor as inoculum to predict the metabolizable energy content of ruminant feeds. The CNCPS fraction analysing ME content of feed samples was carried out in laboratory. Lactating Murrah buffaloes (n = 18) having similar lactation yield (MY 9 kg±2.5) were allotted to three groups in a completely randomised design and fed TMR as per the dietary treatments. The feeding trial was carried out for 3 months and nutrient utilization was analysed. The efficiency of ME utilization in vivo were compared to in vitro gas production and CNCPS fraction. Correlation coefficient (r) between in vitro techniques and in vivo trial in evaluating ME content demonstrated a significantly (P